Decision-Making Deficits Associated with Amyloidosis in Lewy Body Disorders - Spotorno, Nicola; McMillan, Corey T.; Irwin, David J.; Clark, Robin; Lee, Edward B.; Trojanowski, John Q.; Weintraub, Daniel; Grossman, Murray (Frontiers in Human Neuroscience, 2017)
BACKGROUND: Lewy body disorders (LBD) are clinical syndromes characterized by pathological inclusions containing α synuclein. Cognitive deficits are common or diagnostic in LBD, and may be associated with the presence of beta-amyloid (Aβ), which is a hallmark histopathologic abnormality characteristic of Alzheimer’s disease (AD) that can also co-occur with LBD. OBJECTIVE: In the present study we evaluated whether social decision-making difficulties in LBD are associated with Aβ burden. METHODS: Decision-making abilities were measured with a simple, untimed, behavioral task previously validated in patients with behavioral variant frontotemporal dementia, and performance was related to gray matter atrophy on MRI. Aβ burden was assessed by examination of cerebrospinal fluid (CSF) level of Aβ1-42 and by autopsy confirmation in a subgroup of patients. RESULTS: The results revealed that LBD patients with evidence of Aβ have reduced social decision-making abilities compared to patients with no evidence of Aβ. The imaging analysis related greater decision-making difficulty in Aβ-positive patients in respect to Aβ-negative patients to gray matter atrophy in medial orbitofrontal. This region is a critical node of a decision-making network as well as a region previously associated with comorbid α synuclein and Aβ in LBD. CONCLUSIONS: These preliminary findings suggest that cognitive difficulties in LBD extend to include deficits in social decision-making and that this may be related to the presence of Aβ.